Implementation of solar chimney in orang asli settlement in Bukit Lagong Selayang - Leng, Pau Chung (2014)
In compliance with the Malaysia Housing Policy, providing adequate, affordable and quality housing for all is the major goal. The case study house for the study is in the existing settlement for Indigenous people located at Bukit Lagong, Selayang, Kuala Lumpur which was built under the 7th Malaysia Plan (1996-2000). However, the poor thermal performance of the existing house does not satisfy the occupants and cause most of the occupants rather carrying out the daily activities outside the house during the daytime. A field measurement was carried out from 12am of 4 March 2011 to 11pm of 5 March 2011 in order to obtain the real-time data and compared with the CFD simulated result. The experiments followed by introducing solar chimney at the simulation model and examine the result of the thermal performance. The findings show that the thermal performance of the mean air temperature and mean air velocity of the indigenous house has been improved after introducing solar chimney by 2.6% and 15% respectively at the hottest hour compared to the measurement results. This has shown that the solar chimney is useful and functions as the stack ventilation tool in the tropics.